2016
DOI: 10.1055/s-0042-117716
|View full text |Cite
|
Sign up to set email alerts
|

Resilienzförderung während der Wartezeit auf einen Therapieplatz: Evaluation eines Gruppenangebotes im Versorgungssetting

Abstract: High untreated prevalence of mental disorders and long waiting lists for psychotherapy at the same time call for innovative intervention concepts. The positive brief intervention "Personal Model of Resilience" 1 is offered as group training and evaluated for the first time in a naturalistic clinical setting. In a pre-post-design data from 84 wait-list patients are analysed via intention-to-treat (n=84) and completer analysis at 6-week-follow-up (n=54). Repeated measures ANOVAs demonstrate significant improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The results of this study are consistent with previous findings on the PMR: As an option to bridge the waiting time for therapy, the PMR has been shown to be useful as a three-session group intervention [22]. In a study with distressed students in need for counseling, the PMR in a face-to-face setting was superior to a matched control group [23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are consistent with previous findings on the PMR: As an option to bridge the waiting time for therapy, the PMR has been shown to be useful as a three-session group intervention [22]. In a study with distressed students in need for counseling, the PMR in a face-to-face setting was superior to a matched control group [23].…”
Section: Discussionsupporting
confidence: 89%
“…Unlike other effective resilience interventions that focus on establishing new coping strategies [21], the PMR uses strategies that are already available to an individual. In initial studies, the PMR has been shown to be useful while waiting for a therapy [22] or for student counseling [23] where it was administered in three sessions either as group or individual therapy. With small to large effect sizes on dimensions of psychopathology, self-esteem, optimism and well-being, it seems to have a broad outcome profile.…”
Section: Generalize Them To Different Areas Of Lifementioning
confidence: 99%
“…This corresponds to the results of previous studies, which also reported no direct benefit of resource-oriented interventions on depression (Bolier et al, 2013; Teismann et al, 2011). Nevertheless, other studies have demonstrated an antidepressant effect of group therapies with and without a resource-activating focus (Dinger et al, 2020; Feng et al, 2012; Guhn et al, 2021; Huntley et al, 2012; Liwowsky et al, 2014; Okumura & Ichikura, 2014; Steinert et al, 2017; Troesken & Renneberg, 2019; Victor et al, 2016; Weiner et al, 2018). However, these studies did not always examine samples consisting exclusively of patients with affective disorders or did not include control groups.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it was demonstrated that interventions for resource activation had a positive effect on anxiety in Cambodian patients with posttraumatic stress disorder (Steinert et al, 2017) and in combination with cognitive-behavioral therapy in patients with generalized anxiety disorder (Fava et al, 2005). Moreover, a group intervention to build strengths which was conducted during a waiting period for outpatient psychotherapy, proved to be a promising method for patients with affective, anxiety and somatoform disorders in terms of reducing psychopathology and promoting self-esteem (Victor et al, 2016). On the other hand, resource-oriented interventions did not prove to be superior to cognitive therapy in patients with social anxiety with respect to long-term efficacy (Willutzki et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation